PROMOTING COMPETENCE IN MEDIA EDUCATION VIA INNOVATIVE TEACHING METHODS AND DIGITAL TECHNOLOGIES (World Bulletin of Social Sciences, 2026)
This study examines the promotion of competence in media education through innovative teaching methods and digital technologies. It explores how interactive approaches, digital platforms, and multimedia tools enhance students’ critical thinking, media literacy, and practical skills. The research highlights the role of technology in creating engaging and student-centered learning environments. Findings indicate that the integration of innovative pedagogical strategies significantly improves learners’ ability to analyze, create, and communicate media content effectively in a rapidly evolving digital society.